The many hats of transmembrane emp24 domain protein TMED9 in secretory pathway homeostasis - Roberts, Benjamin S.; Satpute-Krishnan, Prasanna (Frontiers in Cell and Developmental Biology, 2023)
The secretory pathway is an intracellular highway for the vesicular transport of newly synthesized proteins that spans the endoplasmic reticulum (ER), Golgi, lysosomes and the cell surface. A variety of cargo receptors, chaperones, and quality control proteins maintain the smooth flow of cargo along this route. Among these is vesicular transport protein TMED9, which belongs to the p24/transmembrane emp24 domain (TMED) family of proteins, and is expressed across vertebrate species. The TMED family is comprised of structurally-related type I transmembrane proteins with a luminal N-terminal Golgi-dynamics (GOLD) domain, a luminal coiled-coil domain, a transmembrane domain and a short cytosolic C-terminal tail that binds COPI and COPII coat proteins. TMED9, like other members of the TMED family, was first identified as an abundant constituent of the COPI and COPII coated vesicles that mediate traffic between the ER and the Golgi. TMED9 is typically purified in hetero-oligomers together with TMED family members, suggesting that it may function as part of a complex. Recently, TMED family members have been discovered to play new roles along the secretory pathway including secreted protein processing, quality control and degradation of misfolded proteins, and post-Golgi trafficking. In particular, TMED9 has been implicated in autophagy, viral replication, and lysosomal sorting, which we will discuss in this Mini-Review.